Reflections on the Destitution Capa city of Social Movements in Latin America (Andamios, Revista de Investigación Social, 2013)
Over recent years, various social movements staged events of magnitude assertive in Latin America, considering the cases of Ecuador, Argentina and Bolivia. In this article we analyze the main dimensions of these groups, to deepen later on their destitution capacity. This research is located within the study-oriented analysis of the social practices logic.  Along the argument we note that the role and deployment of these intermittent motions of the twenty-first century in addition to their innovative actions have highlighted the need to build new interpretive maps for sociological analysis. In conclusion, we postulate that the latent consciousness of people’s power seems to be the key for a better reading of the need to transform the democratic praxis.
Keywords: Social movements; destitution capacity; Latin America; crisis; democracy building